Negotiating Religious Diversity: Islamic Religious Education Teachers as Agents of Rahmatan lil ‘Alamin in Multicultural Schools - Achmad Juaini; Nasron Hakim (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study examines the role and strategies of Islamic Religious Education (IRE) teachers as agents of Rahmatan lil ‘Alamin da’wah in a multicultural public senior high school in East Java, Indonesia. Amid rising identity polarization and social intolerance among adolescents, IRE teachers are increasingly required to move beyond conventional instruction toward communicative and inclusive pedagogical engagement. Using a qualitative case study design, data were collected through in-depth interviews with teachers and school principals, participatory classroom observations, and document analysis. The findings reveal three interconnected roles enacted by IRE teachers: moral exemplars modeling compassionate conduct, facilitators of interfaith and intercultural dialogue, and integrators of universal Islamic values within formal learning processes. Strategies include dialogical and participatory instruction, community-based social projects, and the incorporation of local cultural wisdom to contextualize religious teachings. While curriculum constraints and social media dynamics present structural challenges, the multicultural school environment functions as a dynamic social laboratory for cultivating everyday practices of tolerance. This study contributes to religious education and Islamic communication scholarship by proposing a humanistic da’wah-based educational model grounded in persuasive, dialogical, and inclusive pedagogy, offering a contextual framework for strengthening religious moderation in pluralistic educational settings.